Uninsured in Chicago how the social safety net leaves Latinos behind - Vargas, Robert 1985- (Latina/o Sociology, 2022)
Why millions of Latinx people don't access the healthcare system, even in times of needMore than a decade after the passage of the Affordable Care Act, around eleven million Latinx citizens around the country remain uninsured. In Uninsured in Chicago, Robert Vargas explores the roots of this crisis, showing us why, despite their eligibility, Latinx people are the racial group least likely to enroll in health insurance. Following the lives of forty uninsured Latinx people in Chicago, Vargas provides an up-close look at America's broken healthcare system, and how it impacts marginalized groups. From excruciatingly long waits and expensive medical bills, to humiliating interactions with health navigators and emergency room staff, he shows us why millions of Latinx people avoid the healthcare system, even in times of need. With a compassionate eye, Vargas highlights the unique struggles Latinx people face as the largest racial group without health insurance in the United States. An intimate account of the lives of uninsured Latinos, this book imagines new, powerful ways to strengthen our social safety net to better serve our most vulnerable communities